Metodologi Kajian Filsafat Islam - Rd. Mulyadhi Kartanegara (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 1998)
The methods used in a study significantly determine the results and quality of that study. The better and more appropriate the methods used, the more optimal the quality and results of our research. This writing will discuss four points related to the methodology of philosophical studies in general, and Islamic philosophy in particular. First, it relates to the method of understanding a text, or what is commonly known as the hermeneutic method. Second, it concerns understanding a philosophical idea not as a final product but as a process. Third, it pertains to curriculum development that includes lesser-known but very important figures as links in the development of philosophical ideas, or what is commonly referred to as minor philosophers and also Muslim scientists. Fourth, it relates to the method of analysis or presentation from descriptive to critical methods.